2007
DOI: 10.1029/2004jc002379
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the recurrent coastal sediment plume in Lake Michigan and its impacts on light climate, nutrients, and plankton

Abstract: [1] As part of the Episodic Events Great Lakes Experiment, we sampled total suspended matter (TSM), light climate, nutrients, and plankton along cross-margin transects in southern Lake Michigan during February, March, and April 1998-2000 to capture conditions before, during, and after the occurrence of storm-driven recurrent coastal sediment plumes to define the anatomy of the resuspension events and get insights into their interactions with nutrients and plankton. Variability in timing and strength of winter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 39 publications
3
34
0
Order By: Relevance
“…Projected changes in climate may lead to reduced ice cover in the Great Lakes (e.g., Magnuson et al, 1997) and increased frequency and intensity of extratropical storms (Trenberth et al, 2007). Such a scenario could lead to more intense and extensive RCP events, with profound consequences for ecosystem productivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Projected changes in climate may lead to reduced ice cover in the Great Lakes (e.g., Magnuson et al, 1997) and increased frequency and intensity of extratropical storms (Trenberth et al, 2007). Such a scenario could lead to more intense and extensive RCP events, with profound consequences for ecosystem productivity.…”
Section: Discussionmentioning
confidence: 99%
“…latitude (Trenberth et al, 2007), which would presumably lead to increases in river discharge and delivery of terrestrial materials into the coastal regions. We observed that river discharge exhibited a more localized influence on optical conditions, and presumably biogeochemical conditions, apparently resulting in an enhancement of phytoplankton primary production during periods of high discharge and moderate RCP intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Strong support for a well-mixed water column is given by a number of recent studies, particularly those associated with the Episodic Events Great Lakes Experiment (EEGLE), that clearly demonstrated that properties like chlorophyll concentrations are constant from top to bottom and that currents have the same direction and speed from top to bottom, thus implying a mixed condition (e.g. Fahnenstiel et al, 2000;Beletsky et al, 2003;Rao et al, 2004;Vanderploeg et al, 2007;Kerfoot et al, 2008Kerfoot et al, , 2010.…”
Section: Introductionmentioning
confidence: 92%
“…That is, the protozoans (primarily ciliates), a favored prey of mussels (Lavrentyev et al, 1995), suffered a double blow: direct mortality and reduction of food supply from quagga mussels. Protozoan microzooplankton-primarily ciliateswere identified as a major component of the winter-spring zooplankton community, having a biomass of about the same as the mesozooplankton during 1998-2000 with L. sicilis obtaining 22-74% of its ingested C from the protozoans and the balance from phytoplankton (Bundy et al, 2005;Vanderploeg et al, 2007). As such, they are an important food resource to both diaptomids and Diacyclops.…”
Section: Seasonmentioning
confidence: 99%
“…Sample collection and analysis followed methods described by Vanderploeg et al (2007). In brief, samples were collected using duplicate vertical tows of a 50-cm diameter, 2.5-m long, 153-μm mesh, conical net equipped with an internal calibrated flow meter from 1 to 2 m above the bottom to the surface.…”
Section: Zooplankton Collection and Countingmentioning
confidence: 99%